Social conflict in the execution stage of power generation projects: theoretical elements for a social viability proposal - Mesén Montenegro, Vladimir (2014)
The social effects of power generation projects will be analyzed in this paper, based on the paradigms that conceived such projects and using the theoretical approaches that generate the constructive practices that cover the social world of the communities in the areas of influence and the different persons involved (participants, beneficiaries, affected parties and opponents) and the origin of the different social and environmental conflicts. The article also focuses on how, within this juncture, the project is an external agent that enters the social fabric of one or more communities, generating a series of subjective and objective breakdowns, in a symbolic world of meanings, customs, traditions and forms of psychological and social relationships with the natural and human environment, which are part of the variables that favor social change.